Pengaruh Media Pembelajaran Berbasis Problem Based Learning dan Motivasi terhadap Hasil Belajar Siswa pada Materi Sistem Periodik Unsur Sma Kelas X - Simbolon, Winda D E; Ajat Sudrajat (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out whether there are differences in student learning outcomes taught with PBL-based Powtoon and PBL-based Canva, to find out whether there are differences in student learning outcomes with varying learning motivation on the Periodic System of Elements material, and to see whether there is an interaction between media and learning motivation. on student learning outcomes. This research uses a quasi-experimental method with a 2x2 factorial design, the population is all class X students at SMA N 14 Medan. Samples were taken by random cluster sampling in 2 classes with a total sample of 48 people. Hypothesis testing was carried out using two-way ANOVA at the F level α (0.05). For the PBL-based learning media Powtoon and PBL-based Canva, the Fcount price is 45.77 > Ftable 4.06, which means Ha is accepted, there is a difference in learning outcomes taught with PBL-based Powtoon and PBL-based Canva on the Periodic System of Elements material. In the learning motivation obtained from PBL-based Powtoon media and PBL-based Canva Fcount 42.38 > Ftable 4.06, which means Ha is accepted, there are differences in student learning outcomes with varying learning motivation in the elemental periodic system. Furthermore, for the interaction between media and learning motivation, Fcount is 4.709 > Ftable 4.06, which means that there is an interaction between learning media and students' learning motivation on the periodic system of elements material.